Toward a Contextually Valid Assessment of Partner Violence: Development and Psycho-Sociometric Evaluation of the Gendered Violence in Partnerships Scale (GVPS) - Goessmann, Katharina; Ibrahim, Hawkar; Saupe, Laura B.; Neuner, Frank (Frontiers in Psychology, 2021)
This article presents a new measure for intimate partner violence (IPV), the Gendered Violence in Partnerships Scale (GVPS). The scale was developed in the Middle East with the aim to provide a contextual assessment tool for partner violence against women in violent-torn settings embedded in a patriarchal social structure. In an effort to generate a scale including IPV items relevant to the women of the population, a pragmatic step-wise procedure, with focus group discussions and expert panels, was performed. The study’s analyses resulted in an 18-item checklist featuring four subscales of the GVPS that are based on a new typology of male-to-female partner violence presenting an alternative to the commonly used classification by type of abuse (i.e., physical, psychological, sexual acts). Therein, dominating behaviors, existential threats, impulsive aggression, and aggravated physical assault were identified as reflective of the lived realities of women in the war-torn Middle East, which was confirmed in factor analysis. The scale’s psychometric properties were assessed with data from 1,009 displaced women in Iraq, and associations with measures of psychopathology were determined. Implications for IPV assessment and prevention possibilities in humanitarian contexts and beyond are discussed.